Reliability analysis of repairable systems using system dynamics modeling and simulation - M. Srinivasa Rao; V.N.A. Naikan (Journal of Industrial Engineering International, 2014)
Repairable standby system's study and analysis is an important topic in reliability. Analytical techniques become very complicated and unrealistic especially for modern complex systems. There have been attempts in the literature to evolve more realistic techniques using simulation approach for reliability analysis of systems. This paper proposes a hybrid approach called as Markov system dynamics (MSD) approach which combines the Markov approach with system dynamics simulation approach for reliability analysis and to study the dynamic behavior of systems. This approach will have the advantages of both Markov as well as system dynamics methodologies. The proposed framework is illustrated for a standby system with repair. The results of the simulation when compared with that obtained by traditional Markov analysis clearly validate the MSD approach as an alternative approach for reliability analysis.
Keywords: 650; Simulation approach; Reliability analysis; Dynamic implications of standby systems; Markov system dynamics approach; Complex systems